Gender differences in stress intensity and coping strategies among students, future emergency relief specialists - Gačić, Jasmina; Jović, Sladjana J.; Terzić, Negra S.; Cvetković, Vladimir M.; Terzić, Miloš T.; Stojanović, Dusan G.; Stojanović, Goran R. (Vojnosanitetski pregled, 2021)
Background/Aim. Assisting students face high academic demands which, together with interpersonal, intrapersonal and professional requirements, can be a significant source of stress. The aim of the study was to examine the intensity and frequency of the source of stress, coping strategies and identify gender differences among students, future assisting professionals. Methods. An observational, cross-sectional study was conducted amongst the students of the University of the Belgrade Faculty of Security (Serbia) who, after graduation, will acquire the title of a security manager responsible for human resources in the civil sector. The data were collected in the period October-November 2018. The authorized questionnaire SSM-30 by Jović (Stress scale for the young – 30) was used, which enables students to assess the stress situations intensity on a scale from 1 (minimum) to 10 (maximum intensity). The SSM-30 questionnaire is a combination of the standard Life Events Scale – Holmes Rashe Life Events Scale, also known as the Social Readjustment Rating Scale and life events characteristic for the student population. The questionnaire also included the sample demographic characteristics – gender, and a year of study. The SSM-30 scale includes a list of stressful events and stress coping mechanisms shown in the results. Results. The most common sources of stress in both genders were social and academic ones: death in the family, critical illness in the family, an accident of a person they care about, unwanted pregnancy, lies from close people, disagreement with parents, loss of a study year, crisis, uncertainty after graduation and partner’s infidelity. The most frequently used mechanisms for controlling and overcoming stress were mostly social: talking with friends, listening to music, family support, frequent walks, socializing and going out, using the Internet, frequent sleep, intense physical activity, crying and relaxation. Statistically significant differences between the genders were confirmed – female students demonstrated self-worth of higher intensity during the majority of stressful situations, as they use different stress coping mechanisms from their male students. Conclusion. The results obtained with regard to the assessment of stressors and the use of specific mechanisms for coping point to the need of additional education of students in this field in order to be more focused and open for free professional help, when necessary.